Theorising the Negative Impacts of the Niger Delta Development Commission’s Social Services in Odi Community, Bayelsa State, Nigeria - AKINYOADE, Demola Victor (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2022)
The paper focused on the negative impacts of the Niger Delta Development Commission’s (NDDC) social services in Odi, one of the communities in the Niger Delta. The negative impacts of the social services in Odi are consequences of the mutual interactions of the interventions and the community context. The study employed a case study research design and data were collected through key informant and in-depth interviews, document and observation. Forty participants were interviewed in 60 face-to-face and mobile-phone interviews. Interviews were recorded, transcribed and later analysed using ATLAS.ti 7.0. Findings show that the pervasive perception of the NDDC’s social services as resources triggers feelings of greed and likely deprivation in actors and thus motivated them to struggle for the benefits. This determines and drives the mutual impacts of the social services and the context triggering other negative impacts including the black hole of interactions, malevolent charity-beggar relationship between the Commission and beneficiary community, and oppressiveness and divisiveness of the NDDC interventions. This lends credence to the notion that interventions in conflict context have the potential for negative (conflict exacerbating and peace undermining) impacts.